Performance-Based Incentive for Improving Quality of Maternal Health Services in Bangladesh. (October 2014) - Rob, Ubaidur; Alam, Mohammad Masudul
Poor motivation of providers, primarily caused by low remuneration and/or non-existence of financial incentives, has been a key challenge to improve the quality of maternal health services in the public sector health facilities in rural Bangladesh. An operations research study examined the impact of performance-based incentive for service providers at the institutional level to improve the quality of maternal health services. Quality of care was assessed through monitoring visits of professionals from higher-level health facilities, which contributed to improved service provision within the facilities. Quality scores of the facilities increased from 55% to 78% in 14 months of intervention with significant improvement in antenatal care, postnatal counseling, and institutional delivery ( p < 0.01). Importantly, client satisfaction increased remarkably in the intervention facilities. Performance-based incentive has the potential for motivating service providers in improving the quality of maternal health services and for increasing the utilization of facilities for maternal health services in Bangladesh.